National Policy of Japan for Stimulating Innovation Process in the Energy Industry - Vorobeva, Natalia Alexandrovna; Kolesnikov, Mikhail Vladimirovich (International Journal of Economics and Financial Issues, 2016)
The article explores the main aspects of national policy of Japan for stimulating innovation activity in the energy industry to ensure the national energy security of Japan. Japanese government has decided to renovate the strategy of energy security in a qualitatively higher level, the level of implementation of innovative projects. The following indicators were investigated in dynamics: the structure of the distribution of scientific human capital in the areas of innovative research in Japan; the number of patents in the energy field; the investment in innovation in the energy sphere in Japan. This article also highlights the components of the main areas of innovation in the energy sphere in Japan and it was elaborated the forecasting investment model in innovations in the energy field in Japan until 2025. The results were achieved within the frameworks of the governmental assignment of Russian Ministry of Education and Science in the sphere of scientific research during the researching assignment â„– 26.1478.2014/K “The structural transformation of Russian Economy through the integration installation in the industrial markets of Asia-Pacific Region”. Keywords: Japan, energy industry, innovation, national policy of Japan, innovation project, forecasting investment model in innovations. JEL Classifications: B4, 02, 03, Q4